Discussion Boards as Tools in Blended EFL Learning Programs - Diana Isabel Cantor Barragán (Profile: Issues in Teachers' Professional Development)
This paper reports on a study conducted at Universidad Nacional de Colombia in the ALEX Virtual English program. It shows the main characteristics of discussion boards when used as a main activity in an EFL blended course. The study took place in the second semester of 2008 when the program was in the piloting stage and it illustrates the importance of the discussion board tool in the transition from face-to-face education to virtual education. The research followed the qualitative principles and shows the use given to discussion boards by some of the students of the program. Students’ perceptions of the tool are registered as a description to give the reader the opportunity to develop her/his own perception on its use.